Analisis Efektivitas Program Bantuan Sosial dalam Memutus Rantai Kemiskinan Antargenerasi di Indonesia (Generasi X hingga Generasi Alpha) - Samuel Revaldo Jeverson Siboro; Olive Katrina Joyanka Sihombing; Roma Uli Maria Br Situmeang; Bona Vintura Suyana Pandiangan; Evi Suryani Harahap (STKIP Subang, 2026)
Intergenerational poverty is one of the most complex structural issues in human development in Indonesia. Social assistance programs implemented by the government, such as the Family Hope Program (PKH), Non-Cash Food Assistance (BPNT), and the Smart Indonesia Program (PIP), are expected to be instruments to break the chain of poverty passed down from one generation to the next. This study aims to analyze the effectiveness of social assistance programs in breaking the chain of intergenerational poverty in Indonesia, covering four generations: Generation X (1965–1980), Millennial Generation (1981–1996), Generation Z (1997–2012), and Generation Alpha (2013–2025). The method used is descriptive qualitative research with a literature study approach, utilizing secondary data from the Central Bureau of Statistics, the Ministry of Social Affairs of the Republic of Indonesia, Bappenas, the World Bank, and national and international scientific journals. Data analysis uses the Miles and Huberman model. The research results show that social assistance has partially improved access to education and health care, but its effectiveness in ending intergenerational poverty remains limited due to targeting issues, recipient dependency, regional disparities, and weak program integration with economic empowerment. The novelty of this research lies in its comparative analysis across four generations within a single intergenerational poverty framework, a topic that has not been widely studied before.